Organised cultural encounters: collaboration and intercultural contact in a lullaby choir - Dieckmann, S; Davidson, J (VWB - Verlag für Wissenschaft und Bildung, 2018)
This article examines the early stages of the development of an intercultural lullaby choir in Melbourne, Australia. The community choir emerged from an applied ethnomusicology collaboration between researchers from the Faculty of Fine Arts and Music, The University of Melbourne, and Victorian Cooperative on Children’s Services for Ethnic Groups (VICSEG) New Futures, a not-for-profit community organisation that provides training and support to newly arrived and recently settled migrant communities. The project’s shift from an open-ended exchange of personally meaningful lullabies to a formal ensemble will be interrogated, revealing how ethnomusicological research is defined by the relational dynamics and social arenas within which it is conducted. By way of ethnographic vignettes, this article outlines key stages of the project’s chronological development while also providing insight into participants’ experiences of the resulting musical encounters. Given this dual focus on process and outcome, ethnographic research findings are framed by theoretical work on intercultural contact zones and organised cultural encounters. Sites of intercultural encounter will be brought into view, highlighting how organisational decisions are experienced by participants in corporeal, temporal and affective ways. Like many applied ethnomusicology projects with intercultural objectives, by virtue of its institutionalisation the choir does not embody the transgressive and unexpected characteristics of sites of encounter. At the same time, the sensory embodiment of actively participating in intercultural music-making, learning and teaching manifest key components of “meaningful encounter.” In addition to exploring how participants‘ multiple social identities are constructed, legitimated and challenged in musical contact zones, this paper addresses the procedural, ethical and theoretical methodological implications that have arisen from the research.